Influências do ambiente e da idade sobre a complexidade morfológica dos astrócitos do giro denteado de camundongos suíços albinos - FÔRO, César Augusto Raiol (Universidade Federal do Pará, 2017)
During our previous study (Diniz et al., 2010), mice (Mus musculus) maintained in an impoverished environment that mimicked a sedentary lifestyle from weaning generally performed worse on spatial memory tasks (the Morris water maze) and did not distinguish between old and recent or between displaced and stationary objects in episodic-like memory tests. In contrast, mice maintained in enriched cages for equal time preserved those abilities. These behavioral outcomes were associated with layer-dependent, numerical astrocytic changes. Using the same serial anatomical sections selectively immunolabeled for glial fibrillary acid protein from the previous study, we tested the hypothesis that environmental impoverishment would reduce the morphological complexity of astrocytes, and that such changes would be associated with learning and memory decline. We used three-dimensional microscopic reconstructions and unbiased systematic and random sampling approaches to select astrocytes from the polymorphic, granular, and molecular layers of the dentate gyrus. Cluster and discriminant analysis of three-dimensional astrocytic morphometric features from each layer and experimental group revealed two main morphological phenotypes. Type I astrocytes were more complex than type II; they exhibited larger tree areas, larger tree volumes, more segments, and more vertices. Integrated analysis with previous behavioral findings from the same animals revealed that the reductions in morphological complexity observed in young mice from impoverished and aged mice from enriched environments were observed in both astrocyte types in all layers of the dentate gyrus. We suggest that long-term environmental impoverishment and aging effects on astrocyte plasticity may represent at least part of the circuitry changes underlying learning and memory decline.